2000
DOI: 10.1084/jem.192.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Cc Chemokine Receptor (Ccr)2 Is Required for Langerhans Cell Migration and Localization of T Helper Cell Type 1 (Th1)-Inducing Dendritic Cells

Abstract: There is growing evidence that chemokines and their receptors regulate the movement and interaction of antigen-presenting cells such as dendritic cells (DCs) and T cells. We tested the hypothesis that the CC chemokine receptor (CCR)2 and CCR5 and the chemokine macrophage inflammatory protein (MIP)-1α, a ligand for CCR5, influence DC migration and localization. We found that deficiency of CCR2 but not CCR5 or MIP-1α led to distinct defects in DC biology. Langerhans cell (skin DC) density in CCR2-null mice was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(64 citation statements)
references
References 66 publications
8
55
1
Order By: Relevance
“…*, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001; ****, P Ͻ 0.0001. ments and the localization of the parasite relative to fibroblastic reticular cells (ER-TR7 ϩ ), macrophages (MOMA-2 ϩ ), DCs (CD11c ϩ ), and CD169 ϩ cells at 1 and 3 days postinfection. In prior studies of L. major in CCR2 Ϫ/Ϫ mice, infected cells were localized to the subcapsular sinus of the draining lymph nodes without traversing into the subcortical region (39). In contrast, we found that L. donovani parasites were dispersed throughout the lymph nodes of both CCR2 Ϫ/Ϫ and control mice (Fig.…”
Section: Resultscontrasting
confidence: 47%
See 2 more Smart Citations
“…*, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001; ****, P Ͻ 0.0001. ments and the localization of the parasite relative to fibroblastic reticular cells (ER-TR7 ϩ ), macrophages (MOMA-2 ϩ ), DCs (CD11c ϩ ), and CD169 ϩ cells at 1 and 3 days postinfection. In prior studies of L. major in CCR2 Ϫ/Ϫ mice, infected cells were localized to the subcapsular sinus of the draining lymph nodes without traversing into the subcortical region (39). In contrast, we found that L. donovani parasites were dispersed throughout the lymph nodes of both CCR2 Ϫ/Ϫ and control mice (Fig.…”
Section: Resultscontrasting
confidence: 47%
“…We found that malnutrition dysregulated the two principal chemoattractant pathways (CCR7 with its ligands CCL19 and CCL21 and CCR2 with its ligands CCL2 and CCL7) involved in the recruitment of DCs (39,49,51,52). CCR2, in response to CCL2 and CCL7, also regulates the egress of monocytes from the bone marrow to enter the circulation (53-56) and peripheral lymph nodes via high endothelial venules (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since CCR3 is expressed on cells believed to be involved in Th2 responses and CXCR3 in cells characteristic of the Th1 response (42,43), it was postulated by Weng et al (41) that eotaxin may play a role in the impairment of Th1 responses in pathological conditions. Moreover, CCR2 has also been proposed to be characteristic of cells involved in the development of a Th1 response (44,45), and mice null for CCR2 exhibit a Th2 bias (46 -48). In view of the data we present here, we propose that similar to its antagonistic activity at CXCR3, low nanomolar concentrations of eotaxin, as found in inflammatory settings, may be an important modulator of inflammation and Th1/Th2 bias.…”
Section: Discussionmentioning
confidence: 99%
“…CHIKV infections induce a strongly Th1-biased immune response (10,11), with CCR2 Ϫ/Ϫ mice being reported to have impaired Th1 responses (20,40,41). However, analysis of anti-CHIKV IgG2c (Th1) and IgG1 (Th2) titers (32,42) illustrated that the dominant IgG2c responses were not significantly different in CCR2 Ϫ/Ϫ mice (Fig.…”
Section: Quantitation Of Histology and Immunohistochemistry Of Cellulmentioning
confidence: 99%